Kierunki zmian oddziaływania państwa na innowacyjność kraju w otwartej gospodarce - Zorska, Anna (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The article investigates changes of national innovativeness and state’s innovation policy under conditions of open economy. An external openness – to the global environment – enables growth of international flows of goods and factors as well as increase of business and institutional linkages. Raising importance and impacts of external conditions on national innovativeness and national innovation system (NIS) are driven by four processes: globalization, regionalization, growing knowledge-based economy and transnational business. A new concept of NIS internationalization process in an open economy is introduced, including external and internal conditions, four groups of entities (including ones of foreign origin) together with their linkages and interactions. The return of the state to active innovation policy in order to influence activity led by all entities of domestic as well as foreign origins, including subsidiaries and research centers owned by foreign firms (TNCs) is justified in the light of the research. The state should influence the activity led by foreign entities with instruments of investment policy (to attract inflow of foreign direct investments to the domestic research sector) as well as instruments of innovation policy directed towards all entities.